2021
DOI: 10.1002/aoc.6263
|View full text |Cite
|
Sign up to set email alerts
|

Covalent organic framework supported Pd(II)‐catalyzed conjugate additions of arylboronic acids to α,β‐unsaturated carboxylic acids

Abstract: A palladium(II)‐coordinated covalent organic framework (Pd(II)@COF) was mechanochemically synthesized from [2,2′‐bipyridine]‐5,5′‐diamine (Bpy) and 1,3,5‐triformylphloroglucinol (Tp), which was demonstrated as a catalyst for conjugate addition of arylboronic acids to unreactive α,β‐unsaturated carboxylic acids in aqueous media (water/acetone = 1:1). Modest to good yields were obtained for most substrates, and studies on the catalyst recyclability showed that the heterogeneous catalyst gave >80% yields in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…46E). 225 The yield was maintained at more than 70% after five catalytic cycles. The same year, Ma et al reported an interesting Pd( ii )-loaded COF catalyst based on an imine-linked dual-pore COF which can catalyse regioselective hydrocarbon activation reaction of benzo[ h ]quinoline in a heterogeneous way (Fig.…”
Section: Application Of Metalated Cofsmentioning
confidence: 93%
See 1 more Smart Citation
“…46E). 225 The yield was maintained at more than 70% after five catalytic cycles. The same year, Ma et al reported an interesting Pd( ii )-loaded COF catalyst based on an imine-linked dual-pore COF which can catalyse regioselective hydrocarbon activation reaction of benzo[ h ]quinoline in a heterogeneous way (Fig.…”
Section: Application Of Metalated Cofsmentioning
confidence: 93%
“…224 However, the mechanochemical synthesis can circumvent this issue, but the obtained Pd( ii )-metalated Pd-TpBpy COF has poor crystallinity. 225 In addition, the room temperature synthesis of COFs is also a feasible approach, 226 but may not meet the high crystallinity requirements of most COFs. The attempt to synthesize Re( i )-chelated 2,2′-bipyridine-COFs, however, was successful.…”
Section: Synthetic Strategy Of Metalated Cofsmentioning
confidence: 99%
“…Therefore, refinement of the solvothermal method has been used to increase the crystallinity of the synthesized compound, and, consequently, a refined COF can be obtained. 82…”
Section: Mechanochemical Synthesismentioning
confidence: 99%
“…A range of β-arylated carboxylic acids could be synthesized using Pre-Pd( ii )@COF as a catalyst, in medium to excellent yields (21 to 94%). 67…”
Section: Synthesis and Application Of Pd/cof Catalystsmentioning
confidence: 99%